Efetividade do gluconato de clorexidina a 1% associado à pasta de hidróxido de cálcio (Calen), como medicação intracanal, no combate ao Enterococcus faecalis - Costa, Maíra Pereira de Farias (2006)
This study investigated the occurrence of Enterococcus faecalis in clinical specimens obtained from 25 cases in which endodontic treatment failed and 10 cases of primary endodontic infection, both of which are associated with asymptomatic apical periodontitis. As well, in cases in which it was possible to recover this bacterium, the antibacterial actions of two medications (i) calcium hydroxide based paste (Calen), and (ii) the same mixed with 1% chlorexidine, were evaluated both in vivo and in vitro. Microbiological analysis was performed on the samples collected in the root canal in three phases of the root canal treatment, as follows: (1) before the chemonomechanical instrumentation; (2) after using the intracanal dressing; and (3) after 72 hours of having removed the intracanal dressing, at this period the root canals were empty. The samples were treated according to standard microbiological procedures. The results show that of the twenty-five cases of endodontic re-treatment, E. faecalis occurred in eighteen, and in ten cases of asymptomatic primary endodontic infection, E. faecalis occurred in only two. Also, the results show a higher percentage of occurrence of E. faecalis in teeth in which endodontic treatment failed (72%) compared with cases of primary endodontic infection associated with asymptomatic apical periodontitis (20%). Of the total cases contaminated with E. faecalis, nine were treated with calcium hydroxide based paste (Calen). Of these, six showed the occurrence of E. faecalis on the second sampling, and all the nine cases showed occurrence of this bacterium on the third sampling. Of the total cases contaminated with E. faecalis, eleven were treated with calcium hydroxide based paste (Calen) mixed with 1% chlorexidine. Of these, three showed occurrence of E. faecalis on the second sampling, and two showed occurrence of this bacterium on the third sampling. These results are not conclusive for in vivo experiments, but suggest that calcium hydroxide based paste mixed with 1% chlorexidine combats E. faecalis more effectively than calcium hydroxide alone; however, more certainty will require a larger sample size. For the direct exposure experiment (in vitro), samples of 21 teeth were analyzed. The results show effective antibacterial actions of the two medications to combat E. faecalis -Statistically similar at 95% confidence level.